Syndecan-3 and Notch cooperate in regulating adult myogenesis - Pisconti, Addolorata (The Rockefeller University Press, 2010)
Skeletal muscle postnatal growth and repair depend on satellite cells and are regulated by molecular signals within the satellite cell niche. We investigated the molecular and cellular events that lead to altered myogenesis upon genetic ablation of Syndecan-3, a component of the satellite cell niche. In the absence of Syndecan-3, satellite cells stall in S phase, leading to reduced proliferation, increased cell death, delayed onset of differentiation, and markedly reduced numbers of Pax7(+) satellite cells accompanied by myofiber hypertrophy and an increased number of centrally nucleated myofibers. We show that the aberrant cell cycle and impaired self-renewal of explanted Syndecan-3–null satellite cells are rescued by ectopic expression of the constitutively active Notch intracellular domain. Furthermore, we show that Syndecan-3 interacts with Notch and is required for Notch processing by ADAM17/tumor necrosis factor-α–converting enzyme (TACE) and signal transduction. Together, our data support the conclusion that Syndecan-3 and Notch cooperate in regulating homeostasis of the satellite cell population and myofiber size.